Planning milking facilities for dairy expansion - John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1996)
Construction of a new milking center or remodeling existing milking parlors is a very important decision that can dramatically affect the labor efficiency and profitability of a dairy. Dairy producers should set reasonable goals for present and future needs. All options and configurations of the milking center should be considered and evaluated on a 15-yr planning horizon. Milking parlors should be designed to allow use of a full milking hygiene and add flexibility in management of the parlor.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Expansion; Milking facilities; Construction